FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Shafira Rizqiya (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this research is to examine the influence of leverage, return on asset, company size, sales growth, capital intensity and inventory intensity to tax avoidance. The population of this research is all manufactured companies listed in Indonesia Stock Exchange from 2018 to 2020. Samples are obtained through purposive sampling method, in which only 59 of listed manufactured companies in Indonesia Stock Exchange meet the sampling criterias resulting 177 data available are taken as the samples. The research resource are taken from Indonesia Stock Exchange website. This research used multiple regression method to test the hypothesis. The empirical result indicates return on asset and sales growth have influence to tax avoidance. However leverage, capital intensity, company size and inventory intensity have no influence to tax avoidance